Recent Advances in Atomic Force Microscopy‐Based Local Anodic Oxidation Nanolithography of 2D Materials - Jing Yu; Abdulsalam Aji Suleiman; Jing‐Wen Shi; Ruey Jinq Ong; Francis Chi‐Chung Ling; Weiwen Zhang (Advanced Materials Interfaces)
Abstract 2D materials garner significant research interest due to their unique properties. However, fabricating 2D material electronic devices requires arraying these materials, which often leads to issues like residual photoresist and the need for expensive equipment such as E‐beam and optical lithography. To address these challenges, advanced nanopatterning techniques are essential. Atomic force microscopy (AFM)‐based local anodic oxidation (LAO) is a low‐cost method that avoids photoresist residues and can etch, oxidize, or alter material properties. This review summarizes the development of AFM LAO technology for 2D materials, discussing its reaction mechanisms, applications, and influencing factors. It covers the use of AFM LAO for nanolithography, oxidation, reduction, and device applications in materials like graphene, h‐BN, TMDs, BP, and oxides. The review also examines the challenges and research gaps that remain, including technical obstacles and areas requiring further exploration. Finally, it offers insights into the future prospects of AFM LAO in 2D material‐based nano‐designs and devices, highlighting both its potential advantages and limitations.